If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6y+9=3(2y-3)
We simplify the equation to the form, which is simple to understand
6y+9=3(2y-3)
Reorder the terms in parentheses
6y+9=+(+6y-9)
Remove unnecessary parentheses
+6y+9=+6y-9
We move all terms containing y to the left and all other terms to the right.
+6y-6y=-9-9
We simplify left and right side of the equation.
y=-18
0=-18
The left and right sides are not equal, therefore there is no solution. This equation is invalid.
| X^4-3x^3-12x^2=0 | | 6(5x+4)+3(2x+6)+5=36x+48 | | -0.87y+2=y-0.6 | | -40=-8(8-m) | | -6(x-9)=-42 | | 7+8(4+4x)=6x-39 | | -8a+6a+42=1 | | 4x-3(x-1)=-4+3x+11 | | Fx=10x^2+8x+8 | | 22/2= | | 3x(x^2+2x-6)+4(x^2-6x+2)= | | g(x)=3.4x-8 | | 20n=10n^2 | | 2.2m=19.8 | | 13x+5=-35 | | 6=2(v+8)-4v | | 4(6y+1)+8=6(2y+5)-5 | | 0.9(5x+15)2.5-(x+3)= | | x^6+8y^3= | | (12y^3)+(24y^2)=3y+6 | | X+2x+(2x+30)=280 | | -x=4x-3 | | 4+3x-2=8x+18-3x | | -8=-8(2x-7) | | 93=(93)(63) | | st+3y=6 | | 8-3(1-3m)= | | 1.8+7n=9.5-4bn | | 0.60p+80=0.70+30 | | 2(6x-2)=3(5x-5) | | 6y^2+1y-2=0 | | Y=157.5x+50 |